Building Religious Moderation Through a Behavior Approach to Tolerance and Anti-Radicalism in Adolescents - Nailul Fauziyah; Fina Hidayati (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Teenagers are a generation that continues the nation’s ideals, so it is importantto develop an attitude of peace and tolerance and uphold the unity and unityof the Indonesian nation. However, currently, the survey results show that thelevel of radicalism among adolescents is increasing due to the negative impactof technological advances. This is very important in how adolescents can developreligious moderation as a middle ground in teaching understanding aboutadvocating and applying religious teachings in a balanced and fair manner. Thisresearch aims to build religious moderation through an approach to toleranceand anti-radicalism behavior in adolescents. The method used is a quantitativecorrelation approach. The study’s respondent was taken with purposive samplingtechniques, namely adolescent age (13-16 years), which amounted to 644 people(226 men and 418 women). The results of the analysis showed that toleranceattitudes had an influence of 48.3% or ß = 0.483 with p-value = 0.000, andradicalism had an influence of 26.5% or ß = -0.265 with p-value = 0.000. Theconclusion is to build religious moderation on the evident influence of toleranceand anti-radicalism attitude. With a perspective of accepting differences, andupholding the value of diversity among religious communities is the main capitalin forming an attitude of religious moderation.